Direct-binary-search algorithm for fabrication-tolerant photonic-crystal-like subwavelength structures and its application to a four-mode waveguide crossing in 2 μm waveband. (1st April 2022) - Muratsubaki, Taichi; Fujisawa, Takeshi; Sawada, Yusuke; Sato, Takanori; Saitoh, Kunimasa
Abstract: A novel direct-binary-search algorithm for the design of fabrication-tolerant photonic-crystal-like subwavelength structures is proposed. In the proposed method, structures based on holes with different diameters are considered to enhance the device performance under diameter variation. The usefulness of the proposed method is demonstrated through the design of a fabrication-tolerant four-mode waveguide crossing in the 2 μ m waveband. With the proposed method, the transmission of TE3 mode is increased by 4.9% (for diameter of 130 nm) and 9.5% (for diameter of 150 nm) on average of 15 samples, compared with the conventional direct-binary-search method. The designed device provides insertion losses of <0.87 dB and crosstalks of <−24 dB in spite of diameter variations of ±10 nm from the ideal diameter.